Antipyretic Potential of 80% Methanol Extract and Solvent Fractions of Bersama abyssinica Fresen. (Melianthaceae) Leaves Against Yeast-Induced Pyrexia in Mice - Tegegne BA; Alehegn AA (Dove Medical Press, 2023)
Bantayehu Addis Tegegne,1 Agumas Alemu Alehegn2 1Department of Pharmacy, College of Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Pharmacy, Lumame Primary Hospital, Lumame, EthiopiaCorrespondence: Bantayehu Addis Tegegne, Email bantayehuaddis.90@gmail.comIntroduction: Since fever is a complicated physiological reaction to an infection or aseptic stimulus, finding safer solutions that are more potent and derived from plants is essential to resolving this issue. Bersama abyssinica (Melianthaceae) is traditionally used to treat fever, though this has yet to be proven scientifically.Objective: The present study aimed to assess the antipyretic potential of leaf extract and solvent fractions of B. abyssinica.Methods: The antipyretic activities of crude extract and solvent fractions of B. abyssinica leaves were evaluated using a yeast-induced pyrexia model at three different dose ranges (100mg/kg, 200mg/kg, and 400mg/kg) methanol extract as well as chloroform, ethyl acetate, and aqueous fractions to mice showing an increase in temperature of ≥ 0.5 °C. The rectal temperature of each mouse was recorded using a digital thermometer. To analyze the data, SPSS version 20 and one-way ANOVA followed by Tukey's HSD post hoc test to compare results between groups were utilized.Results: The crude extract demonstrated significant antipyretic potential (P< 0.05 by 100 mg/kg and 200 mg/kg as well as P< 0.01 by 400 mg/kg), with a maximum of 95.06% reduction in rectal temperature at 400 mg/kg, comparable to 98.37% at 2.5 hours by the standard drug. Similarly, all doses of the aqueous fraction, as well as 200 mg/kg and 400 mg/kg doses of the ethyl acetate fractions, resulted in a significant (P< 0.05) reduction in rectal temperature when compared to the corresponding value of the negative control group.Conclusion: Extracts of B. abyssinica leaves were found to have a significant antipyretic effect. Thus, the use of the plant for pyrexia in traditional settings has scientific ground.Keywords: antipyretic activity, extract, fraction, B. abyssinica leaves, yeast-induced pyrexia